Effects of Aspergillus niger on cyanogenic glycosides removal and fermentation qualities of ratooning sorghum - Zhai, Jianrong; Wang, Bo; Sun, Yingpeng; Yang, Jianfeng; Zhou, Junfeng; Wang, Tianyu; Zhang, Wenlan; Qi, Cai; Guo, Yanjun (Frontiers in Microbiology, 2023)
Cyanogenic glycosides (CNglcs) are bioactive plant products involving in plant defense against herbivores by virtue of their abilities to release toxic hydrogen cyanide (HCN). Aspergillus niger has been shown to be effective in producing β-glucosidase, which could degrade CNglcs. However, whether A. niger could remove CNglcs under ensiling conditions is still unknown. In this study, we first investigated the HCN contents in ratooning sorghums for two years, then the sorghums were ensiled with or without the addition of A. niger. Two years’ investigation indicated that the contents of HCN in fresh ratooning sorghum were larger than 801 mg/kg FW (fresh weight), which could not be reduced by silage fermentation under safety threshold (200 mg/kg FW). A. niger could produce β-glucosidase over a range of pH and temperature, which degraded the CNglcs and removed the hydrogen cyanide (HCN) at early days of ratooning sorghum fermentation. The addition of A. niger (2.56 × 107 CFU/mL) altered the microbial community, increased bacterial diversity, improved the nutritive qualities, and reduced the HCN contents in ensiled ratooning sorghum lower than 100 mg/kg FW after 60 days of fermentation. Overall, the addition of 150 mL A. niger + 50 mL sterile water per 3 kg silage could efficiently remove CNglcs from ratooning sorghum silage. In conclusion, A. niger could produce β-glucosidase which degraded the CNglcs during the early days of fermentation, benefiting the ensiling process and improving the utilization of ratooning sorghum.